Letter - Ormaetxea, Pedro de
001-0069-003 BASQUE CHRISTIAN TRADE UNIONS National Committee 25Shrewsbury Road, Redhill, Surrey. 13th July, 1944. The President, National Council of Labour, Transport House, Smith Square, S.W.1. Dear Sir, On behalf of the National Committee of the Basque Christian Trade Unions, the largest workers' organisation in Euzkadi, the Basque Country, I wish to express our sincere gratitude for the statement issued by the National Council of Labour dissociating itself from the Prime Minister's comments on Spain in the recent foreign affairs debate in the House of Commons. Basque workers and democrats in our country fully appreciate the solidarity of the gesture and the comradely feeling shown thereby. Thousands of our trade union members fought for the cause of liberty during the Spanish Civil War, and still stand side by side with the workers of this country in the effort to destroy the forces of tyranny and to establish a better world. It is a great encouragement to us in our exile to see that the British Labour organisations render justice to our cause, and have not forgotten that the defence of our freedom against unprovoked aggression was the prelude to the present world struggle. Yours faithfully P.de Ormaetxea President. 292/946/1/69